DEVELOPMENT OF E-LKPD USING THE FLIPPED CLASSROOM LEARNING MODEL TO ENHANCE ELEMENTARY STUDENTS' LITERACY - Intan Susetyo Kusumo Wardhani; Angga Setiawan; Rohmat Febrianto; Nanda William; Yesita Inka Dela (Jurnal Cakrawala Pendas, 2024)
The purpose of this research is to develop a Flipped Classroom-Based e-LKPD (Electronic Student Worksheet) oriented towards the literacy of elementary school students. The Flipped Classroom-Based e-LKPD is developed to facilitate learning both at home and at school, thereby maximizing students’ literacy training. The research uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model of research and development. Data were collected using student literacy test instruments, questionnaires, and interview sheets with a research sample of 150 students. The results showed that the Flipped Classroom-Based e-LKPD oriented towards literacy is valid and can be used. The validation score percentages from material, media, language experts, and practitioners averaged 97%, categorized as “very valid.” The increase in students’ literacy skills also improved with an average N-Gain score of 0.65. Based on these results, it can be concluded that the Flipped Classroom-Based e-LKPD oriented towards the literacy of elementary school students can be used and is effective in training the literacy skills of elementary school students.